Aspectos evolutivos das proteínas MyD88 e Tollip da via NF-KB - Luiz, Denis Prudêncio (2015)
The innate immune system plays as the first line of defense of all animals. It possesses cells and molecules that act in fighting many types of pathogens. The defense cells carry recognition receptors, which, trigger reactions for the production of molecules that will combat the pathogens. The NF-kB pathway is a pathway conserved in animals, it is part of this system and possesses two important molecules for its operation, MyD88 and Tollip. The role of MyD88 protein is coupling together with other proteins and transmit the signal inside the cell, while Tollip functions as a negative regulator at the end of the same pathway. These two protein sequences were analyzed in different animal species, their evolutionary aspects were studied among the domains of the MyD88 protein, and between the complete sequences and conserved parts of the Tollip. Using bioinformatics tools, we can see that Tollip has successive modifications to optimize its stabilization accumulating aliphatic residues. Differences were found between the stability of primates and arthropods proteins. In addition to the Tollip showing the need for ion Ca2 + for the maintenance of the cavity, it was possible to identify a ligand 768 probably related to inhibition of Tollip. In MyD88 protein we identified a greater identity in sequences of primates in relation to other species analyzed, also it was enhanced the high similarity of some amino acids interface with the functionality of the protein. The TIR domain has demonstrated greater identity between the fields of protein and a greater MydD88 ancestry of its sequence regarding the MD region, which may suggest a relationship with the largest number of interaction partners.